Monetary policy choices in emerging market economies: The case of high productivity growth - Fabio M. Natalucci; Federico Ravenna (University of California, Santa Cruz Institute for International Economics (SCIIE), 2007)
We develop a general equilibrium model of an emerging market economy where productivity growth differentials between tradable and non-tradable sectors result in an equilibrium appreciation of the real exchange ratethe so-called Balassa-Samuelson effect. The paper explores the dynamic properties of this economy and the welfare implications of alternative policy rules. We show that the real exchange rate appreciation limits the range of policy rules that, with a given probability, keep inflation and exchange rate within predetermined numerical targets. We also find that the Balassa-Samuelson effect raises by an order of magnitude the welfare loss associated with policy rules that prescribe active exchange rate management.
Keywords: E52; E31; F02; F41; 330; Balassa-Samuelson effect; optimal monetary policy; exchange rate regimes; emerging markets; European Monetary Union; Aufstrebende Märkte; Allgemeines Gleichgewicht; Produktivität; Handelbares Gut; Nicht-handelbares Gut; Kaufkraftparität; Aufwertung; Balassa-Samuelson Effekt; Theorie